Utilizing mathematical software for the teaching and learning of mathematics in Malaysia - Che Mansor, Naiim Fatimi; Aksah, Saufianim Jana; Mohd Rosli, Nor Aziyatul Izni; Yusof, Khairul Huda; Alshekhly, Mohammed N. Abdulrazaq (Universiti Teknologi MARA, 2025)
The paper examines the effects of mathematical software on the academic performance of secondary school students, along with its roles in facilitating technological adaptation among the students in mathematics education. The study is motivated by persistent challenges in students’ mathematics achievement and the limited integration of technology in classroom practices, despite the increasing availability of digital tools in schools. Two main objectives guided the research are to evaluate the effectiveness of mathematical software in improving students’ comprehension of mathematics, and to measure the extent of technology integration among students in mathematics learning. A quantitative research design was employed, involving 100 student respondents from Sekolah Menengah Kebangsaan Meru, Klang. Data were collected through questionnaires administered via Google Forms after obtaining the necessary approvals. The findings reveal that students using mathematical software reported a 22% improvement in their comprehension levels, along with enhanced flexibility, critical thinking, learning interest, and classroom interactivity. These results underscore the potential of mathematical software not only to strengthen students’ academic performance but also to build their readiness to embrace technology in learning mathematics. The study highlights the importance for educators and policymakers to integrate mathematical software more systematically into pedagogical practices to maximize its educational benefits.